STREM‐1 is elevated in cystic fibrosis and correlates with proteases. Issue 4 (9th January 2017) - Forrester, D.L.; Barr, H.L.; Fogarty, A.; Knox, A.
Summary: Background: sTREM‐1 (soluble triggering receptor expressed on myeloid cells‐1) is a novel inflammatory marker that may be of clinical use in cystic fibrosis (CF). Dysregulation of the TREM pathway has been demonstrated in other inflammatory diseases and modulation in animal models has therapeutic benefit. We hypothesised that sTREM‐1 could act as a biomarker of disease in cystic fibrosis. Methods: Plasma from 17 patients with CF (stable and pre and post pulmonary exacerbation) and eight healthy volunteers was analyzed for sTREM‐1 and proteases (matrix metalloproteinase‐8 (MMP‐8), MMP‐9, and human neutrophil elastase HNE). Results: sTREM‐1 Levels were elevated in stable CF subjects compared to controls (148 pg/ml (130–160) [median(IQR)] vs. 87 (55–118) ( P < 0.01)) but were not further increased during pulmonary exacerbation nor decreased after antibiotic treatment in CF. Protease levels were increased in CF plasma compared to controls: MMP–8 = 3.1 ng/ml (1.5–7.6) vs. 0.3 (0.18–0.53) ( P < 0.01) (Wilcoxon); MMP–9 = 170 ng/ml (124–282) vs. 49 (39–90) ( P < 0.01); HNE = 30.2 ng/ml (22.7–30.9) vs. 17.5 (11.2–22.2) ( P < 0.05). sTREM‐1 correlated positively with protease levels lnMMP‐8 r 2 = 0.55 ( P = 0.08), lnMMP‐9 r 2 = 0.61( P < 0.05), lnHNE r 2 = 0.35 ( P < 0.05). Conclusions: sTREM‐1 is constitutively elevated in CF and positively correlates with protease levels. Modulation of this pathway may be of therapeutic benefit to patients with CF. Pediatr Pulmonol. 2017;52:467–471. © 2017 Wiley Periodicals, Inc.